Implants for surgery - hydroxyapatite - part 2: coatings of hydroxyapatite (ISO 13779-2:2008, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Raj, Caroline; T, Mahadevan; Wong, Darren; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Yusof, Shahril; Manickam, Thirumal; Mohd Yusof, Hyzan; et al. (SIRIM, 2010)
ISO 13779-2:2008 specifies requirements for ceramic hydroxyapatite coatings applied to metallic or non-metallic surgical implants.